Customisable cloud-based IOT monitoring system with smartphone interface - Ang, Cheng Kee (2020)
This project is regarding a growing trend – Internet of Things (IoT). IoT is a collection of multiple things that connected to the Internet and performing data collection, sharing, and processing. As the IoT trend is growing at an incredible speed, people begin to concern about the challenges raised from IoT. For example, security, user-friendliness, privacy, and customizable issues. There are two major problems will be the focus on this project – customisation and user-friendliness. As most of the existing IoT applications are unable to fulfil a user-friendly and customisable IoT monitoring system, there is still a huge learning gap for IoT users in terms of understanding and customising their IoT solution. Some researches and literature reviews are carried out to look deeper into IoT customisation and user-friendliness issues. The reviews of the products including IoT in a Box, EzBlock Studio, RaspController, IoTool, Lego Mindstorm EV3, SimpleLink SensorTag, Xiaomi Home and Skydrop Smart Sprinkler are written in the literature review section of the report. After reviewing the strengths and weaknesses of existing products, a clearer vision regarding the IoT challenges will be presented in the report. The solution of this project is to develop a customisable cloud-based IoT monitoring system with smartphone interface in order to assist users in learning IoT and customising preferable IoT solutions easily. The final product of the project is the combination of IoT hardware, Google Cloud Platform, Firebase and an Android mobile application with the ability to connect, control, monitor and customise users’ IoT solutions.